Time-Variant SRC Kinase Activation Determines Endothelial Permeability Response. Issue 8 (15th August 2019) - Klomp, Jennifer E.; Shaaya, Mark; Matsche, Jacob; Rebiai, Rima; Aaron, Jesse S.; Collins, Kerrie B.; Huyot, Vincent; Gonzalez, Annette M.; Muller, William A.; Chew, Teng-Leong; Malik, Asrar B.; Karginov, Andrei V.
Summary: In the current model of endothelial barrier regulation, the tyrosine kinase SRC is purported to induce disassembly of endothelial adherens junctions (AJs) via phosphorylation of VE cadherin, and thereby increase junctional permeability. Here, using a chemical biology approach to temporally control SRC activation, we show that SRC exerts distinct time-variant effects on the endothelial barrier. We discovered that the immediate effect of SRC activation was to transiently enhance endothelial barrier function as the result of accumulation of VE cadherin at AJs and formation of morphologically distinct reticular AJs. Endothelial barrier enhancement via SRC required phosphorylation of VE cadherin at Y731. In contrast, prolonged SRC activation induced VE cadherin phosphorylation at Y685, resulting in increased endothelial permeability. Thus, time-variant SRC activation differentially phosphorylates VE cadherin and shapes AJs to fine-tune endothelial barrier function. Our work demonstrates important advantages of synthetic biology tools in dissecting complex signaling systems. Graphical Abstract: Highlights: SRC activation causes temporally distinct effects on the endothelial cell barrier Initially, SRC causes endothelial barrier enhancement and VE cadherin rearrangement VE cadherin phosphorylation on Y731 is required for SRC-mediated barrier enhancement Prolonged SRC activity cause barrier disruption Abstract : Klomp et al. used a chemically inducible kinase system and physiological stimuli to demonstrate SRC kinase regulates the endothelial barrier in a temporally dependent manner. SRC activity initially enhances barrier function via the adherens junction protein VE cadherin, while prolonged activity leads to endothelial barrier disruption.